ANALISIS PERUBAHAN SUKU BUNGA , UANG DAN HARGA DALAM KERANGKA KERJA EKONOMI KLASIK - Tahwin, Muhammad (Potensio, 2009)
AbstractAccording to classical economic experts, interest rates are determined by the wishes of the people to make savings and the desire of the entrepreneur to borrow funds for capital investment. Flexibility in interest rates would bring the state in which the amount of savings realized in the economy at full employment is achieved when is equal to the investment that would be entrepreneurs. But now it turns out that the community income level also determines the level of savings. The higher the income, the higher the savings. According to the theory that the added quantity of money supply will cause the same percentage price increase with increasing money supply. While in theory the remaining cash that the accretion of money supply will raise prices on the same level with the added supply of money.Keyword: Interest, Money, and Price